1983
DOI: 10.1038/bjc.1983.108
|View full text |Cite
|
Sign up to set email alerts
|

In vitro genotoxic activities of fibrous erionite

Abstract: A high incidence of mesothelioma has been reported from some villages in Cappadocia, Turkey. This type of cancer is usually associated with the inhalation of asbestos, but on the basis of the most prevalent fibre in the dust from these villages, the Turkish outbreak has been attributed to the inhalation of zeolite fibres. A counter hypothesis, based on the detection of very small quantities of chrysotile and tremolite in strata samples and human lung tissue, postulates a significant role of these minerals as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 20 publications
2
11
0
1
Order By: Relevance
“…Several experimental studies with laboratory animals also confirmed the high carcinogenic potential of erionite, which caused tumors to develop faster than asbestos minerals did (e.g. Suzuki 1982;Maltoni et al 1982;Poole et al 1983;Ozesmi et al 1985;Wagner et al 1985;Coffin et al 1989). The molecular sieving, cation-exchange and catalytic properties of erionite may be possible reasons for this difference in tumorigenesis (Ataman 1978;Coffin et al 1989;Bish and Guthrie 1993).…”
mentioning
confidence: 92%
“…Several experimental studies with laboratory animals also confirmed the high carcinogenic potential of erionite, which caused tumors to develop faster than asbestos minerals did (e.g. Suzuki 1982;Maltoni et al 1982;Poole et al 1983;Ozesmi et al 1985;Wagner et al 1985;Coffin et al 1989). The molecular sieving, cation-exchange and catalytic properties of erionite may be possible reasons for this difference in tumorigenesis (Ataman 1978;Coffin et al 1989;Bish and Guthrie 1993).…”
mentioning
confidence: 92%
“…Kureysler is a village in the western Turkey where tremolite exposure was detected (Coplu et al, 1996). The high potential of erionite to induce MPM has been confirmed by both epidemiological and experimental studies (Artvinli et al, 1979(Artvinli et al, : 1982Barış et al, 1981Barış et al, : 1987Suzuki et al, 1982;Poole et al, 1983;Johnson et al, 1984;Wagner et al, 1985). According to epidemiological studies, the incidence of malignant mesothelioma in erionite villages is 800-1000 times higher than the reported general population incidence elsewhere in the world (Mc Donald et al, 1970: 1977.…”
Section: Introductionmentioning
confidence: 90%
“…Animal data Short-term and mechanistic studies include those of Maltoni et al (1982), Poole et al (1983), Kelsey et al (1986), Palekar et al (1987), Durnev et al (1990Durnev et al ( , 1993, Urano et al (1991), Leanderson and Tagesson (1992), Maples and Johnson (1992), and Valamina et al (1994). Long term animal experimental studies include those of Suzuki and Kohyama (1984), Wagner et al (1985), Maltoni and Minardi (1988), Davis et al (1991), Tatrai et al (1991Tatrai et al ( , 1992, and Carthew et al (1992).…”
Section: Carcinogenic Propertiesmentioning
confidence: 99%